Articles 9.2 And 9.3 of the Civil Code and matrimonial property regimes in Spanish Private International Law. Values, methods and techniques - Calvo Caravaca, Alfonso-Luis; Carrascosa González, Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
This study carries analyzes Articles 9.2 and 9.2 of the Spanish Civil Code and the relationship between both legal provisions. It is highlighted that art. 9.2 CC is the central rule of the system. It is a legal provision norm that has become outdated by giving too much space to the personal Law and not admitting a clear and simple choice of the Law applicable to the effects of marriage and the law applicable to marriage contracts. Both Articles are in full force and are to be applied to marriages celebrated before January 29, 2019. This work maintains that art. 9.3 CC must be understood as a rule that increases the possibilities of validity of marriage contracts in cases involving foreign elements.